The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1965
DOI: 10.1037/h0022437
|View full text |Cite
|
Sign up to set email alerts
|

Proverb word counts as a measure of overinclusiveness in delusional schizophrenics.

Abstract: A partial replication was conducted of Payne's (1964) report concerning the relationship between delusions and overinclusive thinking as measured by proverbs word counts. Word counts were made of Gorhatn Proverbs Test responses given by age-and intelligence-matched groups of 21 delusional schizophrenics, 21 nondelusional schizophrenics, and 21 nonschizophrenic, nondelusional psychiatric in-patients. 23 paranoid, 23 nonparanoid, and 23 nonschizophrenic control Ss, similarly matched, from the same population, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…As expected, we found an impairment in schizophrenia. Our finding of an impairment of proverb comprehension in schizophrenia mirrors numerous classical findings [40, 41, 45]. For example, similar to this study, a seminal investigation by Elmore and Gorham [75] found severe impairments in female patients with schizophrenia when they had to match proverbs with the appropriate alternative meaning in a multiple-choice test, a finding that is confirmed by a substantial number of studies [45].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, we found an impairment in schizophrenia. Our finding of an impairment of proverb comprehension in schizophrenia mirrors numerous classical findings [40, 41, 45]. For example, similar to this study, a seminal investigation by Elmore and Gorham [75] found severe impairments in female patients with schizophrenia when they had to match proverbs with the appropriate alternative meaning in a multiple-choice test, a finding that is confirmed by a substantial number of studies [45].…”
Section: Discussionsupporting
confidence: 90%
“…For example, irony also relates to higher-level language comprehension [10, 3437]. Traditionally [38–40], and as documented by a large body of research [4145], schizophrenia is considered to lead to a deficit in comprehension of nonliteral language. Nonliteral language, such as proverbs, metaphors, and idioms, is interpreted “word by word” (literally) as either wrong or wrong in a particular context.…”
Section: Introductionmentioning
confidence: 99%
“…During evaluation, the patient is asked to explain the meaning of a nonliteral expression with own words and the answer is then rated for its concreteness and other types of formal thought disorder (Brundage & Brookshire, 1995;Gorham, 1956;Wechsler, 1976). This diagnostic procedure has a long tradition within psychiatry (Finckh, 1906;Farrar, 1906;Benjamin, 1944;Gorham, 1956;Goldstein & Salzman, 1965;Andreasen, 1977), but is nevertheless under scrutiny for its reliability. Whereas some studies in younger populations indicated poor retest-reliability (Andreasen, 1977;Burgos, 1986), other studies found better reliability (Reich, 1981) and the same caveat holds for diagnostic validity (Sander & Greenberg, 1968;Andreasen, 1977).…”
Section: Implications For Clinical Practice and Further Researchmentioning
confidence: 99%
“…To our knowledge, there is no quick test available in a clinical setting to check for deficits of figurative interpretation in patients with dementia. In the present study, we assessed the interpretation of a figurative proverb as a clinical test; proverb comprehension is often used to assess the tendency of patients with schizophrenia to provide literal explanations for figurative expressions 3–5 . The aim of the present study was to show the characteristics of proverb comprehension in dementia, and test the hypothesis that suppression of the literal interpretation was required for figurative language interpretation 2,6–8 .…”
Section: Introductionmentioning
confidence: 97%